An overall perspective for the energetic valorization of household food waste using microbial fuel cell technology of its extract, coupled with anaerobic digestion of the solid residue. (15th May 2019) - Antonopoulou, G.; Ntaikou, I.; Pastore, C.; di Bitonto, L.; Bebelis, S.; Lyberatos, G.
Graphical abstract: Highlights: Production of electricity and methane from predried and shredded household food waste (HFW). 11.8 W/m 3 was obtained at an HRT of 18 h, using glucose. For dried HFW, 7.7 W/m 3 or 0.31 MJ/kg TS was obtained. Energy recovery of 12.32 MJ/kg TS DHFW from both processes. Abstract: The valorization of typical household food waste (HFW) produced at municipality level was studied for the production of electricity in a microbial fuel cell (MFC) from its extract, and methane, through anaerobic digestion of the solid extraction residue. HFW, after heat drying and shredding, was subjected to extraction using warm water, which resulted in a liquid fraction (extract) and a solid residue. The rich in soluble chemical oxygen demand extract was used for electricity production in a four air– cathodes single chamber MFC, operating under different organic loading rates, while the solid residue from the extraction process was used as substrate for methane production in biochemical methane potential experiments. On the basis of the energy outputs estimated for the optimum operational conditions of both aforementioned processes, it can be concluded that the exploitation of dried HFW is quite appealing as it leads to promising energy recovery.